O desenvolvimento pragmático de aprendizes de português como língua adicional : as marcas de interação na escrita acadêmica - Tavares, Paulo Ott (2020)
This study aims to investigate the pragmatic development of learners of Portuguese as an additional language (PAL) in academic context through the analysis of the use of interactional markers (stance and engagement) in their writing. It is based on the model of interaction in academic discourse proposed by Hyland (2005a), in which academic writing is conceived as a dialogue in a discourse community. In this perspective, writers use stance markers to express their voices in the text and engagement markers to include their audience as active discourse participants. Stance markers consist of hedges, boosters, attitude markers and self-mentions, while engagement markers encompass reader pronouns, directives, questions, appeals to shared knowledge and personal asides. Based on these categories, the study aims to analyse how PAL learners employ these markers in their writing. In addition, it also aims to compare this use to the one presented by Brazilian students in academic context, in order to find out if there are similarities and differences in the level of interaction in the academic writing of native speakers of Portuguese and learners of PAL in academic context. Moreover, an analysis of the grammatical and lexical development of the PAL learners is also presented, in an attempt to find possible relations between pragmatic development, grammatical development and lexical development. The categories which represent grammatical and lexical development are accuracy and grammatical and lexical complexity. This research is exploratory, since it investigates an aspect of academic writing in PAL which has not been studied before. It is also longitudinal, for it follows a group of participants across a period of time. The participants are four foreign graduate students in a university in Brazil who, throughout an academic semester, wrote four argumentative essays each. Texts from a group of Brazilian university students were also collected to allow for the comparison between these two groups. Results of the research suggest that: the use of interactional markers by the learners of PAL became gradually more homogeneous as time went by; these participants used more interactional markers than the Brazilian participants; the results of the PAL students seem to match the ones found by Hyland (2005a), despite a difference in the distribution of stance and engagement markers. These results point to the possibility of more research to widen this field of study and establish interaction as an analytical category in the studies of academic writing in PAL (and in Portuguese as a native language as well).